THE EFFECT OF DIGITAL LITERACY AND CAREER PLANNING ON THE WORK READINESS OF STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, PADANG STATE UNIVERSITY: PENGARUH LITERASI DIGITAL DAN CAREER PLANNING TERHADAP KESIAPAN KERJA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NEGERI PADANG - Dika Yunilva Aziz; Rani Sofya (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research is in the background by many university graduates who have not yet got a job after graduation. This occurs because there is a gap between the education system and the world of work which results in university graduates being produced not in accordance with the required workforce. For this reason, researchers are interested in knowing the influence of digital literacy and career planning on the work readiness of students of the Faculty of Economics and Business, State University of Padang. This study aims to analyze the influence of digital literacy and career planning on the work readiness of students of the Faculty of Economics and Business The type of research used is causal associative research with a quantitative approach. The population in this study is active S1 students of the Faculty of Economics and Business, State University of Padang with a sample of 356 respondents using proportional random sampling techniques. Data collection in this study is by using a questionnaire. The data analysis techniques used are divided into descriptive analysis, inductive analysis, and multiple linear regression analysis. The results of this study show that the positive and significant influence between digital literacy and career planning on job readiness. This means that the better digital literacy and career planning, the better the job readiness of students will be as well.